An International Validation of a Clinical Tool to Assess Carers’ Quality of Life in Huntington’s Disease - Aubeeluck, Aimee; Stupple, Edward J. N.; Schofield, Malcolm B.; Hughes, Alis C.; van der Meer, Lucienne; Landwehrmeyer, Bernhard; Ho, Aileen K. (Frontiers in Psychology, 2019)
Family carers of individual’s living with Huntington’s Disease (HD) manage a distinct and unique series of difficulties arising from the complex nature of HD. This paper presents the validation of the definitive measure of quality of life for this group. The Huntington’s Disease Quality of Life Battery for carers (HDQoL-C) was expanded and then administered to an international sample of 1716 partners and family carers from 13 countries. In terms of the psychometric properties of the tool, exploratory analysis of half of the sample, demonstrated good internal consistency and reliability. Some items on the full version did not meet psychometric thresholds and a short version (HDQoL-Cs) was developed based on more stringent criteria. Confirmatory Factor Analysis of the model structure showed a good fit for all Factors and, indicated that the HDQoL-C and HDQoL-Cs are psychometrically robust measures of quality of life. We found that carers who lived with and looked after their spouse/partner had reduced sense of coping, hope for the future and overall quality of life. Carers with children who were at risk, carried the gene or were symptomatic also had poorer quality of life outcomes. Findings indicated the HDQoL-C and HDQoL-Cs are valid in multiple languages and across varied cultures as measures of self-reported quality of life in family carers of individual’s living with HD. These psychometrically validated tools can aid and guide the implementation of therapeutic interventions to improve life quality in this population.